Genetic studies of bacterial wilt resistance and agronomic characters, and yield component analysis in tomato - Abdalla, Saad Osman (1996)
Experiments were conducted to evaluate the inheritance and performance of six tomato parental lines (varieties) and their respective cross combinations. Inheritance of bacterial wilt resistance was evaluated in the greenhouse (screening experiment), while assessments of twelve agronomic characters were made under hydroponic conditions. Greenhouse inoculation studies indicated that, parents have different degree of susceptibility to bacterial wilt. There were significant differences (P = 0.01) among genotypes as indicated by their disease index. Studies carried out under hydroponic conditions showed that except for the number of branches per plant and stem diameter, there were significant differences (P = 0.01) among the means of all the characters studied. Different degree of heterosis have been expressed for different characters. For the three populations studied. resistance to bacterial wilt showed high heterosis over mid parental value and no heterosis over better parental value. On the other hand. for most of the agronomic characters in the five populations studied. a majority showed heterosis over better parent, but their values were not high. However. mid parental heterosis values were mostly high. Heritability estimates were generally high for most characters including disease index. This indicated that the additive genes were more important than non-additive genes. Yield characters (viz. number of fruits per plant, average weight per fruit and fruit diameter) were highly and positively correlated with each other. Maturity characters (days to flowering and days to first harvest) were in general negatively correlated with yield. The path coefficient analysis revealed that the number of fruits per plant, average weight per fruit, and fruit diameter were the most important characters that contributed directly to the yield. Therefore. in any breeding programme selection for disease resistant plants (genotypes) after each generation of selfing should also take into consideration other desirable agronomic characters.